2015
DOI: 10.1021/jp512528j
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneously-Alloyed Gold–Silver Nanoparticles as per Feeding Moles

Abstract: Wet-chemical methods involving the coreduction of HAuCl 4 and AgNO 3 have been proven particularly suitable for producing stable Au−Ag alloy NPs with controllable structure−property relationship. However, very poor-solubility of AgCl in aqueous medium and intrinsically different surface energies of Au and Ag remained detrimental-factors in synthesizing so-called "alloy" NPs above the solubility-product of AgCl. Here, we report a robust coreduction procedure for producing citrate-stabilized "homogeneously alloy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 61 publications
4
31
0
Order By: Relevance
“…In the other study, Yin's group fabricated fully alloyed AuAg nanospheres with good compositional homogeneity through the high temperature (≈1000 °C) annealing of SiO 2 ‐coated Au–Ag core–shell nanopolyhedrons. [20b] This method requires complex procedures (e.g., coating and removal of SiO 2 ) and harsh annealing conditions, but more importantly, it cannot produce alloyed nanocrystals with special shapes (e.g., rods, cubes) other than spheres because regardless of their original shape, at such high annealing temperatures, nanocrystals will fuse into spherical particles (see Figure S2, Supporting Information). Therefore, shape‐dependent SPR properties are yet unavailable for homogeneously alloyed nanocrystals synthesized by the existing methods, and their SPRs are confined within the characteristic wavelengths of the Au and Ag spheres (i.e., ≈380–520 nm) …”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the other study, Yin's group fabricated fully alloyed AuAg nanospheres with good compositional homogeneity through the high temperature (≈1000 °C) annealing of SiO 2 ‐coated Au–Ag core–shell nanopolyhedrons. [20b] This method requires complex procedures (e.g., coating and removal of SiO 2 ) and harsh annealing conditions, but more importantly, it cannot produce alloyed nanocrystals with special shapes (e.g., rods, cubes) other than spheres because regardless of their original shape, at such high annealing temperatures, nanocrystals will fuse into spherical particles (see Figure S2, Supporting Information). Therefore, shape‐dependent SPR properties are yet unavailable for homogeneously alloyed nanocrystals synthesized by the existing methods, and their SPRs are confined within the characteristic wavelengths of the Au and Ag spheres (i.e., ≈380–520 nm) …”
Section: Introductionsupporting
confidence: 90%
“…However, these efforts have paid little attention to achieving compositional homogeneity in the crystals produced because they did not consider the chemical stability of Ag. Two recent studies indicated that uniform mixing of Au and Ag atoms (compositional homogeneity) in the nanocrystal is required to achieve the “stabilizing” effect and that Ag remains susceptible to oxidation if the two elements are segregated into large domains (results were verified in this work (vide infra)) . These two studies are currently the only successful examples of the preservation of both plasmonic activity and chemical stability by synthesizing homogeneously alloyed AuAg nanocrystals; however, their synthetic methods were limited to the production of isotropic (nearly spherical) nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical synthesis is just one example of a particularly rapid way of creating various plasmonic nanoparticles. (1)(2)(3)(4)(5)(6)(7) When estimating the optical properties of alloys, weighted averaging of the constants associated with the constituent pure metals is often attempted; however, the results are often inconsistent with observations. We first demonstrated the importance of experimental determinations of the optical constants/permittivity of metals (n = n + ik, ε = ε 1 + iε 2 = n 2 − k 2 + 2ink).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of halides in a reaction mixture can also influence the final composition of NPs, e.g. Au–Ag alloys (Rajendra et al 2015 ). Hence, we wondered whether gold oxide could be an alternative to gold chloride.…”
Section: Introductionmentioning
confidence: 99%